2017
DOI: 10.5539/ibr.v10n12p139
|View full text |Cite
|
Sign up to set email alerts
|

Determining Critical Success Factors that Contribute to the Delay of Water Infrastructure Construction Projects in the Abu Dhabi Emirtae: A Conceptual Framework

Abstract: The purpose of this study is to investigate the relationship between the critical success factors and the critical delays in the context of water infrastructure construction projects (WICPs) in the Abu Dhabi Emirate. In addition, the purpose of this paper is to develop a conceptual model to investigate the potential relationship. The literature concerning the critical success and delay factors and the related models that are available provide a starting point for developing the conceptual model. Based on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, according to Altarawneh, Thiruchelvam & Samadi (2017), due to their frequent use in previous studies and because much researches were concluded their studies results by them in some way, the six most significant success factors in determining project success identified by various number of researchers and their attributes have been chosen for further investigation in this study are listed in Table 1. Owner is committed to release payments within 45 days of invoicing POC2 PM is committed against goals/objectives set to meet project deadlines POC3…”
Section: Critical Success Factors Reviewmentioning
confidence: 99%
“…However, according to Altarawneh, Thiruchelvam & Samadi (2017), due to their frequent use in previous studies and because much researches were concluded their studies results by them in some way, the six most significant success factors in determining project success identified by various number of researchers and their attributes have been chosen for further investigation in this study are listed in Table 1. Owner is committed to release payments within 45 days of invoicing POC2 PM is committed against goals/objectives set to meet project deadlines POC3…”
Section: Critical Success Factors Reviewmentioning
confidence: 99%
“…Sustainability is a significant factor in most facets of infrastructure projects in the construction industry, involving many stakeholders with varying expectations. A considerable amount of research has looked into sustainability in the construction industry with an emphasis on environmental matters [1,12,13].…”
Section: Review Of the Related Literature A Sustainability And Carbon...mentioning
confidence: 99%